Mathematical model of non-isothermal flow of oil through the trunk pipeline - Saltanova, G.; Aisina, Т. (Bulletin of the Karaganda University. Mathematics Series, 2017)
In this article are described a non - isothermal current of high - viscosity oil. A non - isothermal current of viscous liquid on the trunk pipeline it is characteristic of transportation of oil and oil products with preliminary heating from places of production to a customer, of a current of hot water from combined heat and power plant to inhabited arrays and production locations, etc. The one - dimensional mathematical model of a non - isothermal current of viscous liquid and a formula of cost fuel - power expenses for the stationary mode of a current are examined. It is spoken in detail the process of calculation of optimum speed of a current for transportation of high - viscosity oil and oil products in the warmed - up state on pipelines at which the total cost of energy costs of pumping and heating of oil would be minimum.